Open educational resources: higher education students knowledge and use - Alves, Paulo (2018)
Information and communication technologies represent one of the main innovation factors within the teaching and learning process, especially in Higher Education. In this context, the search for building useful and grounded knowledge using strategies which meet students’ needs and interests requires the use of innovative resources, among which we highlight digital educational resources, particularly open educational resources (OER). The open educational resources issue has deserved the attention of teachers, students and institutions. Considering the present situation as well as the importance given to OER and to the role these may play in supporting learning, the aims of this paper are as follows: assess the digital educational resources features most valued by higher education students; verify the extent to which students’ IT knowledge influences their assessment of digital educational resources; identify the knowledge that higher education students have of OER; assess the knowledge that higher education students have of open educational resources platforms. In order to achieve the proposed aims, we focus our attention on open educational resources, starting by assessing digital educational resources’ features as well as the connection between students’ IT knowledge and that same assessment. We also assess the knowledge that higher education students have of OER as well as of their corresponding platforms. The data was obtained through a questionnaire conducted within a sample of 315 students at a Portuguese higher education institution. Among the results obtained, we highlight that the most valued features of digital educational resources are: free access; any time access; allows reuse; and free and open. The results show that there is a positive, low, or very low correlation between students’ IT knowledge and the features associated with digital educational resources. In addition to this, the results show an almost inexistent knowledge of the OER concept and of their uses as well as of the existing OER platforms. The data indicates that there is still a long way to go so that OER may be part of the resources used by students to improve their learning.